5. Implicit Theories of Intelligence and School Performance. A Systematic Review - Vechiu Adina-Petronela; Popa Nicoleta Laura (Sciendo, 2022)
The aim of this paper was to shed a light upon the relationships between implicit theories of intelligence and school performance through a systematic review approach, which mainly used empirical studies on the connections between these constructs. In the first section of this review, we synthesized the necessary theoretical marks for understanding the concepts mentioned above, we analysed definitions, as well as models of implicit theories of intelligence, referring to the relevance for the educational field. Then, there is also an analysis on empirical studies in the international literature that addresses the central concepts of the paper in an educational context and a systematic review of the relationships between implicit theories of intelligence and school performance. The last section contains the final conclusions, the limits of this systematic review and future research directions.